International consensus on the most useful assessments used by physical therapists to evaluate patients with temporomandibular disorders: A Delphi study. (4th May 2020) - von Piekartz, Harry; Schwiddessen, Julius; Reineke, Lukas; Armijo‐Olivio, Susan; Bevilaqua‐Grossi, Débora; Biasotto Gonzalez, Daniela A.; Carvalho, Gabriela; Chaput, Eve; Cox, Erin; Fernández‐de‐las‐Peñas, Cesar; Gadotti, Inae Caroline; Gil Martínez, Alfonso; et al.
Abstract: Objective: To identify assessment tools used to evaluate patients with temporomandibular disorders (TMD) considered to be clinically most useful by a panel of international experts in TMD physical therapy (PT). Methods: A Delphi survey method administered to a panel of international experts in TMD PT was conducted over three rounds from October 2017 to June 2018. The initial contact was made by email. Participation was voluntary. An e‐survey, according to the Checklist for Reporting Results of Internet E‐Surveys (CHERRIES), was posted using SurveyMonkey for each round. Percentages of responses were analysed for each question from each round of the Delphi survey administrations. Results: Twenty‐three experts (completion rate: 23/25) completed all three rounds of the survey for three clinical test categories: 1) questionnaires, 2) pain screening tools and 3) physical examination tests. The following was the consensus‐based decision regarding the identification of the clinically most useful assessments. (1) Four of 9 questionnaires were identified: Jaw Functional Limitation (JFL‐8), Mandibular Function Impairment Questionnaire (MFIQ), Tampa Scale for Kinesiophobia for Temporomandibular disorders (TSK/TMD) and the neck disability index (NDI). (2) Three of 8 identified pain screening tests: visual analog scale (VAS), numeric pain rating scale (NRS) and pain during mandibular movements. (3) Eight of 18 identified physical examination tests: physiological temporomandibular joint (TMJ) movements, trigger point (TrP) palpation of the masticatory muscles, TrP palpation away from the masticatory system, accessory movements, articular palpation, noise detection during movement, manual screening of the cervical spine and the Neck Flexor Muscle Endurance Test. Conclusion: After three rounds in this Delphi survey, the results of the most used assessment tools by TMD PT experts were established. They proved to be founded on test construct, test psychometric properties (reliability/validity) and expert preference for test clusters. A concordance with the screening tools of the diagnostic criteria of TMD consortium was noted. Findings may be used to guide policymaking purposes and future diagnostic research.